Responses of sorghum to cold stress: A review focused on molecular breeding - Vera Hernández, Pedro Fernando; Mendoza Onofre, Leopoldo Ernesto; Rosas Cárdenas, Flor de Fátima (Frontiers in Plant Science, 2023)
Climate change has led to the search for strategies to acclimatize plants to various abiotic stressors, to ensure the production and quality of crops of commercial interest. Sorghum is the fifth most important cereal crop providing several uses including human food, animal feed, bioenergy, or industrial applications. The crop has excellent adaptation potential to different types of abiotic stresses, such as drought, high salinity, and high temperatures. However, it is susceptible to low temperatures compared to other monocotyledonous species. Here, we have reviewed and discussed some of the research and advances focused on the physiological, metabolic, and molecular mechanisms determining sorghum cold tolerance to improve our understanding of the nature of such trait. Questions and opportunities for a comprehensive approach to clarify sorghum cold tolerance or susceptibility are also discussed.